Subspecies-specific response to ACTH challenge test in the house mouse (Mus musculus) - Daniszová, K; Mikula, O; Macholán, M; Pospíšilová, I; Vošlajerová Bímová, B; Hiadlovská, Z (General and comparative endocrinology, 2017)
Long term changes in hormonal levels of small and rare animal species can be effectively monitored by non-invasive methods such as immunoenzymatic analysis. These methods generally analyze metabolites instead of the hormone itself and thus do not invade the organism. However, they can be influenced by many factors, so before they are used, they need to be validated. For this purpose we used the "ACTH challenge" test based on stimulating the animal's adrenocortical activity and measuring the consequent increase of the level of its glucocorticoid ("stress") hormones. Specifically, we measured concentrations of fecal glucocorticoid metabolites of two house mouse subspecies, Mus musculus musculus and M. m. domesticus. Using polyclonal antibody we investigated the mice's naturally occurring circadian fluctuation and their reaction to the adrenal stimulation. This study confirmed that the selected method is suitable for analysis of fecal corticosterone metabolites in the wild house mouse. More importantly, we revealed a subspecies-specific stress response at the level of corticosterone production: while the significant effect of ACTH was proved in both subspecies, a notable adrenocortical reaction was also elicited by injecting the saline solution in M. m. domesticus. Our results thus highlight the importance of considering potential cryptic variation within the species under study when designing projects on adrenal stress hormone assessments.
Keywords: kortikosteron; zeměpis; feces; druhová specificita; Geography; Female; Corticosterone; Mouse; zvířata; Europe; myši; Hormone metabolites; adrenokortikotropní hormon; Mice; Feces; ženské pohlaví; ACTH challenge; Male; Species Specificity; Noninvasive monitoring; Endocrine activity; Animals; mužské pohlaví; Evropa; Adrenocorticotropic Hormone